(untitled) (Discourse of Law and Administration, 2023)
With the elections of November 2023 Poland might get a new government. After its victory, this new government would face a crucial dilemma. How should it deal with the messed-up judicial system? Should it take the sledgehammer and simply dismiss all judges appointed in violation of EU law? We suggest a more constrained approach. To restore an independent judiciary and – in a broader perspective – the rule of law, it would suffice to remove the central perpetrators from the judiciary. To achieve this aim, we plead for the criminal responsibility of judges who seriously and intentionally disrespect EU values. Establishing their criminal responsibility would go hand in hand with their removal from office. This proposal, however, relies on one central premise: the judicial applicability of Article 2 TEU values. Ten years ago, this judicial applicability might have seemed legal science fiction. Under the pressure of illiberal developments in several Member States, however, the Court has started to operationalise the values enshrined in Article 2 TEU. Today, it is clear that this provision contains legal obligations. We argue that national judges who seriously and intentionally disregard these obligations must be hold criminally accountable.